Pembelajaran Mufradat dalam Meningkatkan Maharah al-Kalam Santri di Pondok Pesantren - Suandi Munthe; Bambang Bambang; Abdul Halim Hanafi (IAI Muhammadiyah Sinjai, 2022)
The model of learning Arabic in islamic boarding schools has differences from those in madrasas, just like those in the Al-Ashry Islamic boarding school in Padang City, Arabic is taught separately or based on branch theory. This kind of Arabic learning system will have an impact on the results achieved by students. Therefore, this study aims to determine the learning of mufradat and the improvement of maharah al-kalam learners. The research was conducted with a qualitative approach, data were collected through observation, interviews and documentation studies. The research data was analyzed with interactive techniques, namely analyzing data by communicating the data obtained through the techniques used and connecting the data obtained from different informants. The result of the study was that mufradat learning at the Al-Ashry Islamic boarding school was carried out with a separate system, namely separate from other elements in Arabic, the learning resource in mufradat learning was the yellow books. Learners has an increase in maharah al-kalam, the increase is seen in the skill of pronouncing vocabulary precisely, the richness of vocabulary.